Catching the Big Fish – Fish-Sauce Containers from the Republican Era to Late Antiquity in Nea Paphos (Cyprus) - Oleksiak, Jerzy M. (Rei Cretariae Romanae Fautorum Acta, 2024)
Garum production sites of the Republican Period, as well as multiple kiln workshops of transport amphorae used for carrying fish-sauce, are well attested in Sicily and on the North African coast. New ceramic evidence provided by numerous fragments of transport vessels collected from Late Hellenistic layers of the Agora in Nea Paphos, Cyprus, offers a unique opportunity to elucidate the still understudied period of economic exchange between the two of most important islands of the Mediterranean Sea. Late Hellenistic Tubular Amphorae, one of the most numerous types of central Mediterranean transport vessel imports within the assemblage gathered in Nea Paphos, enable us to trace mutual contact between the heart of the Republican world and Cyprus under Ptolemaic rule at the dawn of Roman economic, political and military dominance in the Eastern Mediterranean. A detailed consideration of the vessels and therefore of the origins of garum, based on comprehensive macro-observation of the gathered material, will be complemented by a typological and chronological discussion.